Gene Expression During the Development of Bacteriophage φ29 III. Analysis of Viral-Specific Protein Synthesis with Suppressible Mutants - McGuire, Jeffrey C. (1974)
Fifty-four suppressible mutants of bacteriophage φ29 have been isolated with a variety of mutagens and assigned to eight complementation groups. Viral-specific protein synthesis in UV light-irradiated, nonsuppressing Bacillus subtilis 60084 was analyzed with exponential acrylamide gels. Four additional φ29 proteins which were undetected on ordinary acrylamide gels are reported in this paper. Five phage φ29 proteins have been unambiguously assigned to specific cistrons. Two cistrons had pleiotropic effects on viral protein synthesis. Mutants in cistrons I or II were unable to synthesize DNA in nonsuppressing bacteria. Mutants in cistron I were unable to attach viral chromosomes to the host cell membrane, and the protein responsible for this function has been identified. The other viral protein playing a role in phage φ29 DNA synthesis is also identified and assigned to cistron II. Mutants in cistron II can attach viral chromosomes to membrane, but cannot synthesize DNA in nonsuppressing bacteria.